Identification of Maturity-Onset Diabetes of the Young Caused by Mutation in FOXM1 via Whole-Exome Sequencing in Northern China - Zhong, Liang; Zhao, Zengyi; Hu, Qingshan; Li, Yang; Zhao, Weili; Li, Chuang; Xu, Yunqiang; Rong, Ruijuan; Zhang, Jing; Zhang, Zifeng; Li, Nan; Liu, Zanchao (Frontiers in Endocrinology, 2021)
Diabetes mellitus is a highly heterogeneous disorder encompassing different types with particular clinical manifestations, while maturity-onset diabetes of the young (MODY) is an early-onset monogenenic diabetes. Most genetic predisposition of MODY has been identified in European and American populations. A large number of Chinese individuals are misdiagnosed due to defects of unknown genes. In this study, we analyzed the genetic and clinical characteristics of the Northern China. A total of 200 diabetic patients, including 10 suspected MODY subjects, were enrolled, and the mutational analysis of monogenic genes was performed by whole-exome sequencing and confirmed by familial information and Sanger sequencing. We found that clinical features and genetic characteristics have varied widely between MODY and other diabetic subjects in Northern China. FOXM1, a key molecule in the proliferation of pancreatic B-cells, has a rare mutation rs535471991, which leads to instability within the phosphorylated domain that impairs its function. Our findings indicate that FOXM1 may play a critical role in MODY, which could reduce the misdiagnose rate and provide promising therapy for MODY patients.